High Purity cis-Cinnamic Acid Preparation for Studying Physiological Role of trans-Cinnamic and cis-Cinnamic Acids in Higher Plants - Salum, Maria Laura (2013)
Cinnamic acids are present in all kinds of plant tissues and as consequence in herbs and derived medicines, cosmetics, foods, etc. The interest in study their role in nature and possible health effect on consumers has grown exponentially. Because of their molecular structure they can exist in both trans- and cis-forms, having both found in plants. However, as only the trans-forms are commercially available very few studies in vitro and in vivo of the cis-role are available. In the present review the current knowledge in this field of studies is summarized including the brief description of a new tool for easy and friendly synthesis of cis-cinnamic acids by researchers in order to be able to conduct new experiments.